2011
DOI: 10.1016/j.marpolbul.2011.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Toothed whales in the northwestern Mediterranean: Insight into their feeding ecology using chemical tracers

Abstract: a b s t r a c tRisso's dolphins, pilot whales and sperm whales rarely strand in the northwestern Mediterranean. Thus, their feeding ecology, through the analysis of stomach contents, is poorly known. The aim of this study was to gain further insight into the segregation/superposition of the diet and habitat of Risso's dolphins, pilot whales and sperm whales using chemical tracers, namely, stable isotopes (d N values were obtained in Risso's dolphins (11.7 ± 0.7‰), sperm whales (10.8 ± 0.3‰) and pilot whales (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 66 publications
2
32
1
Order By: Relevance
“…Indeed, fin whales mainly forage during summer on a small euphausiacean, Meganyctyphanes norvegica (Bentaleb et al, 2011;Druon et al, 2012), while long-finned pilot whales and sperm whales are teuthophageous, feeding exclusively or preferentially on bathypelagic cephalopods of the Histioteuthidae and Ommastrephidae family (Astruc and Beaubrun, 2005;Praca and Gannier, 2008). Stomach content analysis from stranding events in the French and Italian coasts, showed that sperm whales are true specialists in terms of food selection, as 90% of their diet consists on species of the Histioteuthidae family (Praca and Gannier, 2008;Praca et al, 2011). Long-finned pilot whales are more generalist feeders as 40-50% of their diet consists of Todarodes sagittatus, 10-20 % of H. bonnelii and H. reversa and 10% is made up by several other prey species (Praca and Gannier, 2008;Praca et al, 2011).…”
Section: Diet and Trophic Positionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, fin whales mainly forage during summer on a small euphausiacean, Meganyctyphanes norvegica (Bentaleb et al, 2011;Druon et al, 2012), while long-finned pilot whales and sperm whales are teuthophageous, feeding exclusively or preferentially on bathypelagic cephalopods of the Histioteuthidae and Ommastrephidae family (Astruc and Beaubrun, 2005;Praca and Gannier, 2008). Stomach content analysis from stranding events in the French and Italian coasts, showed that sperm whales are true specialists in terms of food selection, as 90% of their diet consists on species of the Histioteuthidae family (Praca and Gannier, 2008;Praca et al, 2011). Long-finned pilot whales are more generalist feeders as 40-50% of their diet consists of Todarodes sagittatus, 10-20 % of H. bonnelii and H. reversa and 10% is made up by several other prey species (Praca and Gannier, 2008;Praca et al, 2011).…”
Section: Diet and Trophic Positionmentioning
confidence: 99%
“…Beside the threat of POPs potential hazard to marine mammal populations, the levels and profile of these contaminants can serve as an intrinsic marker from which population structure can be defined (Praca et al, 2011;Ryan et al, 2013b). Indeed, these compounds reflect the ecosystem conditions under which marine mammals live and feed and therefore can infer their geographical distribution (Aguilar et al, 2002;Borrell et al, 2006;Praca et al, 2011).…”
mentioning
confidence: 99%
See 3 more Smart Citations